2018
DOI: 10.3390/ijms19071894
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary RNA-Seq Analysis of Long Non-Coding RNAs Expressed in Human Term Placenta

Abstract: Development of particular structures and proper functioning of the placenta are under the influence of sophisticated pathways, controlled by the expression of substantial genes that are additionally regulated by long non-coding RNAs (lncRNAs). To date, the expression profile of lncRNA in human term placenta has not been fully established. This study was conducted to characterize the lncRNA expression profile in human term placenta and to verify whether there are differences in the transcriptomic profile betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 99 publications
7
19
0
Order By: Relevance
“…These lncRNAs were characterized by shorter transcript length, longer exons, lower estimated number of exons and lower expression levels. These properties were also observed in other reported lncRNAs within the genome [20,[35][36][37].…”
Section: Discussionsupporting
confidence: 85%
“…These lncRNAs were characterized by shorter transcript length, longer exons, lower estimated number of exons and lower expression levels. These properties were also observed in other reported lncRNAs within the genome [20,[35][36][37].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, they are usually smaller than mRNAs, for example, one study showed that lncRNA exhibit an average length of 1900 nt and that more than 30% of lncRNAs are in the range of 500-1000 nt. (Majewska et al 2018). Similarly, this study shows that lncRNA contain lower number of exons, as 38% of lncRNAs possess only 2 exons, while only 0.31% of lncRNAs had over 10 exons (Majewska et al 2018).…”
supporting
confidence: 72%
“…(Majewska et al 2018). Similarly, this study shows that lncRNA contain lower number of exons, as 38% of lncRNAs possess only 2 exons, while only 0.31% of lncRNAs had over 10 exons (Majewska et al 2018). In GENCODE v7 database, 42% of lncRNAs have two exons compared with 6% of protein-coding genes, while the median length equals 592 bp compared with 2453bp for protein-coding transcript (Derrien et al 2012).…”
supporting
confidence: 63%
“…One of the major functions of lncRNAs is to recruit/inhibit transcription factors (TFs) to the promoter of their targeting genes. 40 , 41 Although the transcriptome sequencing has revealed a large number of lncRNAs in normal human placenta, 42 we do not know to what extent the lncRNAs might be involved in PE. In order to search for lncRNAs involved in PE, our group has recently carried out a transcriptome sequencing on placentae from patients with early-onset severe PE (EOSPE) and normal controls and identified 383 lncRNAs differentially expressed.…”
Section: Introductionmentioning
confidence: 99%